"A Confusion of Glory": Orthodox Visitors as Sources for Muscovite Musical Practice (Late 16th-mid 17th century) - Papadopoulos, George-Julius; Jensen, Claudia (Intersections, 2005)
Greek and other Orthodox travelers to Russia were important and knowledgeable witnesses to Muscovite liturgical singing practices. This article surveys several Greek sources from around 1600: a poem and a memoir by Archbishop Arsenios of Elasson (1550-1626); a poem describing events connected with the False Dmitrii (1606) by Matthaios Koletzides; and a report of the Moscow trip undertaken by Theophanes, Patriarch of Jerusalem (1619). We also consider the lengthy narrative by Paul of Aleppo, who accompanied Patriarch Makarios of Antioch to Moscow (1650s and 1660s). All of these sources provide rich examples of continuing exchanges among Russian and foreign Orthodox singers throughout this period.